Tea intake and total body bone mineral density of all ages: a Mendelian randomization analysis - Xing, Chen; Tan, Yanrong; Ni, Wentao (Frontiers in Nutrition, 2024)
Background: There is increasing evidence indicating that tea intake affects bone mineral density levels; however, the causality between tea intake and bone mineral density is inconclusive. The aim of this study was to assess the causal relationship between tea intake and total body bone mineral density (TB-BMD) through two-sample mendelian randomization (MR) analysis. Methods: We conducted a two-sample MR approach to estimate potential causal effects of tea intake on TB-BMD at all ages in a European population. The analyses were performed using summary statistics obtained for single-nucleotide polymorphisms (SNPs) identified from a genome-wide association meta-analysis of tea intake (N = up to 447,485 individuals) and from the GEnetic Factors for Osteoporosis (GEFOS) consortium’s genome-wide association meta-analysis (N = up to 56,284 individuals), with baseline data collected from 2018 and populations derived from the European. The association of each SNP with TB-BMD was weighted by its association with tea intake, and estimates were combined mainly using an inverse-variance weighted meta-analysis. Besides, we explored the potential causal effects between green tea intake, herbal tea intake, and TB-BMD. Results: The MR analysis revealed genetically determined tea intake exert a causal impact on TB-BMD, with the odds ratio (OR) of 1.204 (95% CI: 1.062-1.366, P = 0.004), especially in the age of 45-60 (OR = 1.360, 95% CI: 1.088-1.700, P = 0.007). No horizontal pleiotropy and heterogeneity were not observed. However, there were no causal effect of tea intake on TB-BMD in the age of 0-15, 15-30, 30-45, and over 60. In the subgroup analysis, when green tea or herbal tea were regarded as the exposure factors, no salient associations were found between green tea or herbal tea consumption and TB-BMD (IVW P = 0.368). Similarly, there was also no causal association between herbal tea intake and TB-BMD (IVW P = 0.264). Conclusions: The findings of this study support the evidence that tea consumption increases bone density and reduces the risk of osteoporosis in 45-60 ages of European population.